Gender Differences in Body Mass Index, Body Weight Perception, weight satisfaction, disordered eating and Weight control strategies among Indian Medical and Nursing Undergraduates - Poreddi Vijayalakshmi; Rohini Thimmaiah; S. Sai Nikhil Reddy; Kathyayani B.V; Sailaxmi Gandhi; Suresh BadaMath (Investigación y Educación en Enfermería, 2017)
Objective. To assess gender disparity in body weight perception, Body Mass Index (BMI),  eight satisfaction and role of depression among undergraduate Medical and Nursing  students.